Vaccination during pregnancy by race/ethnicity: a focus on American Indians/Alaska NativesAJOG Global Reports at a Glance - Christen L. Jarshaw, MD; Osariemen Omoregie, MBBS, MPH; Jennifer D. Peck, PhD; Stephanie Pierce, MD, MS; Emily J. Jones, PhD, RNC-OB; Pardis Hosseinzadeh, MD; LaTasha B. Craig, MD (Elsevier, 2024)
BACKGROUND: Vaccination during pregnancy reduces the incidence of infections and their associated adverse outcomes in both mothers and infants. The American College of Obstetricians and Gynecologists has recommended influenza and Tdap vaccination during pregnancy since 2004 and 2013, respectively. Several studies have examined disparities in vaccination rates during pregnancy by race/ethnicity. However, none have included American Indians/Alaska Natives as a specific racial/ethnic group on a national level. Current literature suggests that American Indian/Alaska Native infants experience increased morbidity and mortality from both influenza and pertussis infections compared with most other groups in the United States. OBJECTIVE: This study aimed to evaluate the uptake of influenza and Tdap vaccinations during pregnancy by race/ethnicity, with a specific focus on American Indian/Alaska Native people. STUDY DESIGN: This cross-sectional study used data from the Pregnancy Risk Assessment Monitoring System. Comparisons of vaccine uptake across racial/ethnic groups (American Indian/Alaska Native, Asian, non-Hispanic Black, non-Hispanic White, Hispanic, and "None of the above") were evaluated using weighted logistic regression analyses to estimate prevalence odds ratios with 95% confidence intervals. Models were adjusted for maternal age, parity, maternal education, marital status, payment method at delivery, prenatal care in first trimester, maternal smoking status, Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) participation, and receipt of influenza vaccine reported by a health care provider. RESULTS: For both vaccines, Asian respondents had the highest uptake (influenza, 70.1%; Tdap, 68.2%), whereas Black respondents reported the lowest uptake (influenza, 44.4%; Tdap, 57.9%). For the influenza vaccine, American Indian/Alaska Native respondents demonstrated a higher uptake compared with White respondents, and the magnitude of difference increased markedly after adjusting for respondent characteristics (adjusted odds ratio, 1.74; 95% confidence interval, 1.58-1.90). In the unadjusted analyses, Black individuals reported influenza vaccination at approximately half the rate of their White counterparts during pregnancy. This effect was attenuated but remained lower after adjustment for respondent characteristics (adjusted odds ratio, 0.73; 95% confidence interval, 0.70-0.76). For the Tdap vaccine, American Indian/Alaska Native respondents reported lower uptake than White respondents; however, this difference disappeared when adjusted for respondent characteristics (adjusted odds ratio, 0.99; 95% confidence interval, 0.83-1.19). Asian and Hispanic respondents displayed a similar uptake compared with their White counterparts for both vaccines. CONCLUSION: Our findings indicate that there are racial/ethnic disparities in influenza and Tdap vaccination rates among pregnant individuals in the United States. Demonstration of increased uptake among American Indian/Alaska Native people in the crude analysis may reflect the success of various public health interventions through Tribal and Indian Health Service hospitals. Nonetheless, vaccination status during pregnancy remains seriously below national guideline recommendations. Greater measures must be taken to support preventative care in marginalized populations, with particular emphasis on community-driven solutions rooted in justice.